IMPROVEMENT OF COORDINATION OF MOVEMENTS BY MEANS OF RHYTHMIC GYMNASTICS - Natalia Grudnitskaya (Вестник Северо-Кавказского федерального университета)
The article deals with the problem of developing the coordination abilities of adolescent girls in extracurricular rhythmic gymnastics classes. For this purpose, a program of rhythmic gymnastics with a primary focus on the development of coordination abilities was developed and theoretically justified. It was assumed that the inclusion in the rhythmic gymnastics classes of hip-hop elements, special rhythmic movements subordinate to a certain tempo and rhythm ofperformance of various music, elements of yoga and special exercises by the method of Tabata can effectively influence the improvement of the corresponding coordination abilities of girls. As a result of the research, the high efficiency of the developed program for the development of the coordination abilities of girls aged 13-14 by means of rhythmic gymnastics was revealed.